APPLICATION OF CENTRAL COMPOSITE DESIGN AND RESPONSE SURFACE METHODOLOGY FOR OPTIMIZATION OF METAL ORGANIC FRAMEWORK: NOVEL CARRIER FOR DRUG DELIVERY - PREETI KUSH; JITENDER MADAN; PARVEEN KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present study is to optimize the synthesis method of metal-organic framework (MOF) for high yield and larger surface area with minimum size for efficient drug loading. Materials and Methods: Materials of Institute Lavoisier (MIL)-101-NH2 was synthesized by microwave-assisted hydrothermal method. Central composite design (CCD) under response surface methodology (RSM) was used for optimization. Process optimization was done by validating the model to obtain maximum surface area, maximum yield, and minimum particle size. Final obtained formulation was characterized by particle size and zeta potential, scanning electron microscopy, powder X-ray diffraction, Fourier-transform infrared spectroscopy, Brunauer–Emmett–Teller, and thermogravimetric analysis. Furthermore, gemcitabine (GEM) was used as a model drug for encapsulation in these MOFs for drug delivery carriers. Results: The results revealed that MIL-101-NH2 of average size-158 nm with high yield (70%) and high surface area (2347 m2/g) could be produced easily and reproducibly at a selected condition. This enhances the drug delivery application of the valuable MIL-101-NH2. Optimized values for these parameters were 170°C, 5.00, and 1:1:400 for temperature, pH, and reactant ratio, respectively. MIL-101-NH2 appeared as a promising carrier for GEM delivery with higher encapsulation (77.7±2%) and loading (22.6±2%). Conclusion: The results conclude that processing parameters such as temperature pH and reactant concentration obtained from CCD-RSM significantly affect the main constraints, i.e., surface area, particle size, and yield. The faster encapsulation of GEM in MOF makes them a promising carrier for drug delivery application.